Drivers of employee creativity of the banking industry in Bangladesh: a case study on Shahjalal Islami Bank Limited (SJIBL) - Munsur, Md. Seam (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.